Can changes in land use in a semi-arid region of Brazil cause seasonal variation in energy partitioning and evapotranspiration? - Santos, Wilma Roberta dos; Jardim, Alexandre Maniçoba da Rosa Ferraz [UNESP]; Souza, Luciana Sandra Bastos de; Souza, Carlos André Alves de; Morais, José Edson Florentino de; Alves, Cleber Pereira; Araujo Júnior, George do Nascimento; Silva, Marcelo José da; Salvador, Kaique Renan da Silva; Silva, Marcos Vinícius da; Morellato, Leonor Patricia Cerdeira [UNESP]; Silva, Thieres George Freire da (Elsevier, 2024)
Changes to forests due to deforestation, or their replacement by agricultural areas, alter evapotranspiration and the partitioning of available energy. This study investigated seasonal variations in the energy balance and evapotranspiration in landscapes under different levels of anthropogenic intervention in the semi-arid region of Brazil. Micrometeorological data was obtained from September 2020 to October 2022 for three areas of the semi-arid region: preserved Caatinga (CAA, native vegetation), Caatinga under regeneration (REGE) and a deforested area (DEFA). Here, we use the Bowen ratio energy balance method. Measurements were taken of global solar radiation, air temperature, relative humidity, vapour pressure deficit, rainfall, net radiation, latent heat flux, sensible heat flux, soil heat flux, evapotranspiration, volumetric soil water content and Normalised Difference Vegetation Index. Sensible heat flux was the dominant flux in both areas with 66% for preserved Caatinga vegetation, 63% for Caatinga under regeneration and 62% deforested area. The latent heat flux was equivalent to 28% of the net radiation for preserved Caatinga vegetation, Caatinga under regeneration and deforested area. The evapotranspiration in turn responded as a function of water availability, being higher during the rainy seasons, with average values of 1.82 mm day−1 for preserved Caatinga vegetation, 2.26 mm day−1 for Caatinga under regeneration and 1.25 mm day−1 for deforested area. The Bowen ratio presented values > 1 in deforested area, preserved Caatinga vegetation and Caatinga under regeneration. Thus, it can be concluded that the change in land use alters the energy balance components, promoting reductions in available energy and latent and sensible heat fluxes during the rainy-dry transition in the deforested area. In addition, the seasonality of energy fluxes depends on water availability in the environment.
Keywords: Dry forest; Land use; Surface energy budget; Turbulent heat fluxes